Evaluation of Some Minerals Content of Drinking and River Water in Iraq by AAS Method - Mustafa A. Kadhim1, Abd-alussain Sh. Naji1 , Luay S. Khaleefah1 , Hayder N. Salman1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The experiment was conducted during 2018 to evaluate to the presence of certain elements (Lead, Copper, Chromium, Zinc, Nickel, Cadmium, Arsine and mercury) in Tab and Bottled water in addition to riverbed and cliff water. The obtained data were compared with the corresponding international and national guideline values. The concentration of Tap and Bottled water samples for Cr and As were higher than the permitted concentration established by FAO/WHO scoring (0.0623, 0.3120)and (0.0680, 0.448) respectively. Whilst Zn, Ni, Pb, Hg, Cd, and Cu were lower than the permitted concentration established by FAO/WHO for both samples Tab and Bottled water which scored (0.0608, 0.0550, 0.0075, 0.00589, 0.0013 and nil) and (0.0420, 0.0152, 0.0105, 0.00581, 0.0003 and nil) respectively. Thus, the concentrations of As in both River bed and cliff water samples were higher than the permitted concentration established by the Iraqi (C.O.S.Q.C) Central Organization for Standardization and Quality Control which scored (0.754 and 0.245) respectively. Regarding the rest of the element which Seem to be lower than the permitted concentration established by Central Organization for Standardization and Quality Control in Iraq for Riverbed and cliff.